Trading life: organ trafficking, illicit networks, and exploitation - Columb, Seán (Stanford University Press, 2020)
Excavating the organ trade -- The illegal trade in organs -- Organ trading networks -- Disqualified bodies -- Exodus -- Organ(ized) crime -- Regulating the organ trade.